Investigation of surface integrity in laser-assisted machining of nickel based superalloy - Xu, Dongdong; Liao, Zhirong; Axinte, Dragos; Sarasua, Jon Ander; M'Saoubi, Rachid; Wretland, Anders (2020)
While laser-assisted machining can significantly improve the machinability of nickel-based superalloy, the mechanism of surface integrity evolution and its influence on the material functional performance is still not clear. The present study gives a comprehensive investigation on the surface integrity of laser-assisted milling (LAMill) process with an in-depth study of the mechanism of chip formation, microstructural and mechanical alternations, supported by key outcomes from the two constitutive processes, conventional milling (CMill) and single laser scanning (LS). Although the high thermal affected layer in LAMill process has been removed through the cutting chips, a significant bending effect has been found in both the LAMill and LS workpiece. More interestingly, a combined impact of the residual stress from LS and CMill has been found on LAMill workpiece while a lattice evolution has been revealed regarding both the thermal and mechanical influence. Specifically, inadequate fatigue performance on LAMill and LS workpiece has been found due to the high thermal effect in the superficial layer regarding the residual tensile stress distribution and microstructure variation. While LAMill is generally considered as a promising machining method with improved machinability of difficult-to-cut materials, this research shows a poor workpiece functional performance (fatigue) and justifies its application prospect.